GERAKAN AKSI BELA ISLAM - Tri Handayani (STIQ al-Lathifiyyah Palembang, 2020)
Aksi Bela Islam or Act of Islamic Defense is a series of rallies in Indonesia and other countries often triggered by expressions or attitudes that show displeasure and contempt for Islam. The actions occurred as the public's response to the government being slow to deal with and process perpetrators of